Youtube-Based Instruction in Teaching Speaking English in An Indonesian Senior High School - Jabu, Baso; Kurniadi, Muslimah; Abduh, Amirullah (Celebes Journal of Language Studies, 2023)
The study was experimental research. The thesis was intended to found out two research question. The first was the effectiveness of using YouTube-based instruction in teaching speaking English in an Indonesian Senior High School. The second was the interest of the students in the use of YouTube in learning speaking English. The population in this research was all of the students’ class XII Mipa 1 SMAN 14 Makassar as an experiment group that consist of 34 students. The data of this research was obtained by the result test and questionnaire on the subject for pretest and posttest. The data was analyzed by analysis of SPSS 2013. Based on analysis of statistic, the researcher found that YouTube-based instruction in teaching speaking English made students better understood in the material in learning in the classroom and increased all aspects of speaking English by score of t test was -22.277, standard deviation was 5.284, n-gain score was 56.12 categorized “effective enough” and 31 students got score more than KKM. The interest of the students in the use of YouTube in learning speaking English as a media at SMAN 14 Makassar with the mean score was 65.4 that categorized “very high”.